Thermodynamic and kinetic stability. Properties of micelles and vesicles formed by the decanoic acid/decanoate system - K., Morigaki; P., Walde; Misran, M.; H., Robinson B. (2003)
The dialysis of micellar and vesicular systems, through a cellulose acetate membrane permeable only to monomer surfactant, has been investigated for the system sodium decanoate/decanoic acid as a function of pH, in pH regions where micelles (pH 9) or vesicles (pH 7.5) are present. The results provide data that are helpful in establishing the thermodynamic state of the systems and the interplay of the relevant equilibrium and kinetic considerations. Additionally, the kinetics of spontaneous formation and destruction of vesicles when subjected to a pH-jump perturbation have been studied. Changes are rapid, taking place over a time scale of a few seconds.